Influence of base stacking geometry on the nature of excited states in G-quadruplexes : a time-dependent DFT study - Phan, Anh Tuân (2015)
G-quadruplexes are four-stranded structures of nucleic acids that are formed from the association of guanine nucleobases into cyclical arrangements known as tetrads. G-quadruplexes are involved in a host of biological processes and are of interest in nanomaterial applications. However, not much is known about their electronic properties. In this paper, we analyze electronic excited states of G-quadruplexes using a combination of time-dependent DFT calculations and molecular dynamics simulations. We systematically consider experimentally observed arrangements of stacked guanine tetrads. The effects of structural features on exciton delocalization and photoinduced charge separation are explored using a quantitative analysis of the transition electron density. It is shown that collective coherent excitations shared between two guanine nucleobases dominate in the absorption spectrum of stacked G-tetrads. These excitations may also include a significant contribution of charge transfer states. Large variation in exciton localization is also observed between different structures with a general propensity toward localization between two bases. We reveal large differences in how charge separation occurs within different nucleobase arrangements, with some geometries favoring separation within a single tetrad and others favoring separation between tetrads. We also investigate the effects of the coordinating K+ ion located in the central cavity of G-quadruplexes on the relative excited state properties of such systems. Our results demonstrate how the nature of excited states in G-quadruplexes depends on the nucleobase stacking geometry resulting from the mutual arrangement of guanine tetrads.